Pollution havens? Carbon taxes, globalization, and the geography of emissions - Christofer Schroeder; Livio Stracca (European Central Bank (ECB), 2023)
This paper studies the impact of national carbon taxes on CO2 emissions. To do so, we run local projections on a cross-country panel dataset, matching measures of emissions of carbon dioxide with information on the introduction of carbon taxes and their implied price. Importantly, we consider both measures of territorial emissions - emissions emitted within a country's borders - and consumption emissions - emissions emitted anywhere in the world to satisfy domestic demand. We find that carbon taxes reduce territorial emissions over time, but have no significant effect on consumption emissions. Our estimates are robust to propensity-score weighting adjustments and are driven by countries which are more open to trade. Carbon taxes also lead to a modest increase in imports, suggesting that international trade may imply a negative carbon externality. Together, our findings highlight the limitations of national carbon taxes in isolation and the importance of international cooperation in reducing global emissions.
Keywords: F18; F64; H23; Q58; 330; carbon taxes; emissions; carbon leakage